Role of delta-like 4 in solid tumours and response to radiation therapy - Bham, S (2013)
Delta-like ligand 4 (DLL4) is a ligand for the Notch family of receptors. DLL4 is an important regulator of angiogenesis and DLL4 blockade promotes non-productive angiogenesis and delays tumour growth. The aim of this thesis was to investigate the effects of anti-DLL4 therapy in solid tumours in combination with a clinically relevant dose of ionising radiation (5 Gy; IR) and to analyse alterations in the Notch pathway induced by the treatments. Combining both treatments resulted in a greater than additive tumour growth delay in LS174T tumours, compared to either treatment alone. DLL4 blockade dysregulated vasculature and increased necrosis in LS174T and HCT-15 (DLL4-expressing and negative cell lines respectively) tumours within 3 days after treatment, but no changes were observed with IR alone. Additionally, combined IR and anti-DLL4 treatment of FaDu tumours (another DLL4-negative cell line) by our colleagues, also resulted in a supra-additive growth delay. These results show that combining IR with DLL4 blockade is an effective strategy for prolonging tumour growth delay and suggest that the stroma/vasculature provide the main therapeutic target for the anti-DLL4 therapy. Analysis of Notch pathway shows that IR upregulated Jag1 in tumour cells, and may inhibit Notch and downregulate DLL4 in the stroma. These changes may potentially affect tumour vessels and response to anti-DLL4 therapy. In vitro, anti-DLL4 therapy induced proliferation in quiescent contact-inhibited endothelial cells and also appeared to abrogate IR-induced inhibition of migration. These results suggest that DLL4 may be important in maintaining vessel quiescence and that IR may in part decrease migration through Notch signalling. Combining IR and DLL4 blockade to target tumour growth is an effective and well tolerated strategy and warrants further validation and refinement to be translated into clinical practice.